(untitled) (Bangladesh Journal of Medical Science, 2024)
Paracentral acute middle maculopathy (PAMM) is identified by the occurrence of an inner nuclear layer (INL) hyperreflective band on optical coherence tomography (OCT), which was subsequently accompanied by INL atrophy. A multitude of systemic diseases and vasculopathy risk factors have been linked to PAMM. PAMM, which has been associated with infection with Coronavirus disease 2019(COVID 19), may indicate post-infectious complications. By influencing vascular endothelial cells, COVID-19 infection can induce an inflammatory and procoagulatory state, resulting in vascular thromboembolic complications, although the precise mechanisms underlying these complications remain unknown. Thus, the present review explores and discusses about paracentral acute middle maculopathy, its diagnosis and treatment and adds a note on its implications after the outbreak of COVID 19. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S115-S121